Application of diffusive gradients in thin-films for in-situ monitoring of nitrochlorobenzene compounds in aquatic environments. (15th June 2019) - Zhang, Delin; Zhu, Yuanting; Xie, Xianchuan; Han, Chao; Zhang, Hao; Zhou, Lijun; Li, Meng; Xu, Guizhou; Jiang, Lu; Li, Aimin
Abstract: Nitrochlorobenzene compounds (NCBs) are of key interest in environmental monitoring due to their high toxicity. To better understand the presence and fate of NCBs in aquatic environments, an in-situ sampling technique of diffusive gradients in thin films (DGT) based on hydrophilic-lipophilic-balanced (HLB) resin, combined with gas chromatography, was developed to measure four typical NCBs, e.g. meta-chloronitrobenzene (MNCB), para-chloronitrobenzene (PNCB), ortho-chloronitrobenzene (ONCB), and 2, 4-dinitrochlorobenzene (CDNB). The diffusion coefficients of MNCB, PNCB, ONCB, and CDNB in agarose-based gel were firstly determined in diffusion cell experiments and ranged from 7.19 × 10 −6 to 7.49 × 10 −6 cm/s. The capacities of HLB-DGT for MNCB, PNCB, ONCB, and CDNB were higher than 114.65, 117.52, 117.72, and 37.58 μg/cm 2, respectively. The HLB-DGT performance on NCBs determination was demonstrated to be independent of natural fluctuations in pH (3–9), ionic strength (0.001–0.5 M), and dissolved organic matter concentrations (0–20 mg/L) and of deployment time (0–120 h). In the field application, the DGT-based method to measure NCBs not only proved to be accurate and effective, but also performed better than the grab sampling method under the variable conditions. This study demonstrates that the newly developed in-situ method based on DGT can provide an attractive alternative for the routine monitoring of NCBs in aquatic environments. Graphical abstract: Image 1 Highlights: A newly in situ method based on DGT for NCBs measurement is presented. The diffusion coefficients of NCBs through agarose-gel are firstly reported. The DGT method is independent of a wide range of environmental factors. The DGT method is robust, effective, and highly sensitive.